Stabilisasi Tanah Dengan Menggunakan Bahan Tambah Abu Sekam Padi (Studi Kasus: Tanah Desa Gunung Nona Pensip, Kecamatan Nusaniwe, Kota Ambon) - Gilberth Marcel Pattipeiluhu; Sjafrudin Latar; Goedfried Lewakabessy (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
Soil is a primary element in construction as it serves as the foundation for buildings, roads, and bridges. In the village of Gunung Nona Pensip, the condition of the soil foundation, which consists of layers of coral rock, needs to be evaluated as it may not meet technical requirements. This study was conducted by adding rice husk ash (RHA) as a stabilizing material due to its high silica content, which has pozzolanic properties, potentially enhancing soil strength. The method used was an experimental method in the laboratory with variations in rice husk ash content of 3%, 6%, and 9%. Soil samples were tested using the CBR (California Bearing Ratio) test under conditions without curing and after 7 and 14 days of curing. The main parameters observed included CBR values, optimum moisture content, and maximum density. Test results showed that the addition of rice husk ash could increase soil CBR. The 9% mixture without curing produced a CBR value of 4.42%, increased to 6.07% after 7 days, and reached a maximum value of 6.60% after 14 days of curing. This demonstrates that rice husk ash is effective for enhancing the bearing capacity of clay soil and can be applied as an alternative material in the field.